The Effect of Sowing Time and Nutrient Supply on the Yield Stability of Maize - El Hallof, Nóra; Sárvári, Mihály (Acta Agraria Debreceniensis, 2004)
Sowing time, nutrient supply and plant number play crucial roles in the yield stability of maize. The productivity of various hybrids, each with its own genetic characteristics, was tested for three different sowing times and five different fertilizer doses. The highest yields were achieved at the third sowing time (17. V.), which is unusual, because the second half of the summer was rainy and was favourable for late sowing. The seed moisture content at harvest was higher than the optimal 14-15% at the third sowing time, the hybrids, which have intensive bleeding dynamics, couldn’t reach the lower seed moisture content at harvest of the early sowing. In that case we have to decision whether the plus yield of the third sowing time cover the drying costs. Some hybrids produced the highest yields by N 120, P2O5 75, K2O 90 kg/ha active agent but the higher fertilizer doses depress the yield. The other part of the hybrids were able to produce high yield by bigger fertilizer doses. On the whole the agro-ecological optimum of the NPK fertilization was N 120-160, P 25-100, K 90-120 kg/ha active agent, but the N 80, P2O5 50, K2O 60 kg/ha fertilizer doses was the most effective.